Growth and Distribution of Frequency Long Fish (Decapterus sp) Catching Products In Iner And Outside Waters Of Bara Buru District - Maluku - Abdussabar Polanunu; Samsia Umasugi; M. Chairul Basrun Umanailo (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The waters of Bara Bay as one of the small pelagic fishing areas in Buru Regency have considerable potential. Fishing efforts carried out by small fishermen using traditional fishing gear such as gill nets and long line have changed along with the development of fishing technology so that studies are needed related to standing stock and the dynamics of fish resource populations. This study aims to determine the growth and frequency distribution patterns of Layang fish (Decapterus sp) and to compare body lengths of fish caught outside the bay and in the bay of Bara. The result study showed that the highest frequency distribution of Layang (Decapterus sp) fish was outside the bay at 208-218 mm, and the location in the bay was 168-179 mm in length. The growth pattern of Layang fish (Decapterus sp) at both catchment locations (Outside Bay and in the bay) is negative allometric meaning that the length growth is faster than the weight growth.The relationship between fish length and weight was very strong with value R = 0.995 at the Outside Bay catchment area and an R = 0.983 value at the Inside Bay catchment location. There is a difference in the length of the Layang fish (Decapterus sp) caught outside the bay and inside the bay with a significant value of p<0.05 where the average length of the Layang fish (Decapterus sp) outside the Bay is greater (215.876 mm) than the average length of Layang fish (Decapterus sp) in the inside Bay (193.661 mm).